Museu de arte sacra de Pernambuco: seu histórico e seu acervo. - Penha, Cássia Teixeira da (2019)
This dissertation aims to study the Museum of Sacred Art of Pernambuco, the exhibition rooms and its collection (sacred and religious elements). The purpose of this study is to demarcate the viability of both the space and the aforementioned collection, in order to know to contribute to the formation of students of basic education. With this, it is presumed that these students, intermediated by the teacher, would have a contact with the museum, based on a prior knowledge of that visiting environment. MASPE is a public institution, installed in a building listed by IPHAN, whose restoration counted on the partnership of FUNDARPE, body responsible for safeguarding the collection of objects of the Archdiocese of Olinda and Recife and providing services to society through the valorization and recognition of the patrimony sacred Christian. In the study, it was necessary to trace the profile of MASPE, a museum created from the agreement signed between the Foundation of the Historical and Artistic Patrimony of Pernambuco and the Archdiocese of Olinda and Recife. It is a cultural space with a collection composed of sacred and religious articles. Many of his images were part of the churches and brotherhoods of Olinda, dating from the seventeenth to the twentieth century, which present characteristics of local civil and religious society. It completes the collection, objects and images of the current century. This historical and religious representation of Pernambuco and Brazilian society corroborates the ongoing investigation of these public spaces in order to ensure that new generations can enjoy the cultural space. Research was carried out on the museum, art and education institution, the city of Olinda, the religious bias of this historical municipality and the MASPE, in the organizational, educational and social aspects. It was verified that the space offers an adequate layout of its collection, which justifies the study of the teacher or researcher, so that it makes viable, through mediation, the fundamental knowledge prior to the visiting students.